Allylic C–H functionalization via group 9 π-allyl intermediates. Issue 40 (10th September 2020) - Nelson, Taylor A. F.; Hollerbach, Michael R.; Blakey, Simon B.
Abstract : This perspective presents an analysis of how reagent choice impacts mechanism and regioselectivity in group 9-catalysed allylic C–H functionalization. Abstract : Allylic C–H functionalization catalysed by group 9 Cp* transition-metal complexes has recently gained significant attention. These reactions have expanded allylic C–H functionalization to include di- and trisubstituted olefins, and a broad range of coupling partners. More specifically, several catalytic C–N, C–O, and C–C bond forming allylic C–H functionalization reactions have been reported, proceeding via MCp*-π-allyl intermediates. Herein we present an overview of these reactions by mechanistic paradigm. We also place this information in context of recent advances, as well as, limitations that remain for this class of reactions.